THE CONNECTION BETWEEN EMPLOYEE COMPETENCE AND BUSINESS SUSTAINABILITY IN RIVERS STATE'S BANKING INDUSTRY - Nwinyokpugi, N. Patrick; Dinee, Torbeebari Gift (Journal of Allied Research in Management and Entrepreneurship (JARME), 2023)
Employee competence is an essential aspect of business sustainability in today's competitive world, especially in the banking sector in Nigeria. Employees' competence is affected by factors such as communication skills, competence, social skills, adaptations for employee growth, technical skills, and social relations for job rotations. However, Nigerian banks are faced with the problem of low employee competence, which leads to increased employee turnover and reduced global competitiveness. This study explores the relationship between employee competence and business sustainability in the banking industry in Rivers State. The study utilized a quantitative research design, and 240 employees were selected through simple random sampling. The data were collected using a questionnaire and analyzed using structural equation modeling. The findings reveal that communication skills, competence, social skills, adaptations for employee growth, technical skills, and social relations for job rotations have a significant positive relationship with business sustainability. The study recommends that banks prioritize employee competence by investing in training and development programs, encouraging creativity and innovations, promoting social relations and communication skills, and supporting employee growth through job rotations. Furthermore, banks are encouraged to adopt sustainability policies that can promote financial performance, employee satisfaction, and environmental protection.